The behavior of the Bucharest Stock Exchange during the current financial markets crisis and proposed measures for its sustainable development - PANAIT, Iulian; LUPU, Iulia (Annals of Spiru Haret University. Economic Series, 2016)
Our day to day study of the Romanian stock market during the period July 2007 – September 2009 revealed in many cases a specific behavior. Although all the emerging markets from the region evolved in correlation with the more established exchanges, the negative impact of the crisis on our exchange was in many aspects deeper and more powerful than it should have been if we look at the actual macro and micro economic situation, considering the empirical evidence that the capital market is positively correlated with the long term economic growth. We think that this overreaction to the negative side is the direct result of the lack of maturity of our local exchange (in terms of capitalization, liquidity, participants, legislation and surveillance) and we propose a few measures that are supposed to render a sustainable development and may improve its stability during times of financial turbulences.